2008
DOI: 10.1016/j.jtcvs.2008.01.040
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic and chamber-specific mitochondrial remodeling in right ventricular hypertrophy can be therapeutically targeted

Abstract: The dynamic changes in mitochondrial membrane potential during right ventricular hypertrophy are chamber-specific, associated with activation of NFAT, and can be pharmacologically reversed leading to improved contractility. This mitochondrial remodeling might provide a framework for development of novel right ventricle-specific therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 40 publications
3
76
1
Order By: Relevance
“…In contrast in RV-PAB there was downregulation of transcripts for actin and cytoskeleton protein binding, intracellular transport, and the sarcomere and myofibril. This would agree with previous reports that have suggested that in RV hypertrophy, mitochondrial and metabolic remodeling are the predominant changes in growing animals as well as in adult hypertrophy models (1,6,27,32). The downregulation of these mechanoskeletal processes occurring in the RV but not in the LV would account for the more rapid progression to contractile failure in RV-PAB compared with LV-AOB.…”
Section: H704supporting
confidence: 92%
“…In contrast in RV-PAB there was downregulation of transcripts for actin and cytoskeleton protein binding, intracellular transport, and the sarcomere and myofibril. This would agree with previous reports that have suggested that in RV hypertrophy, mitochondrial and metabolic remodeling are the predominant changes in growing animals as well as in adult hypertrophy models (1,6,27,32). The downregulation of these mechanoskeletal processes occurring in the RV but not in the LV would account for the more rapid progression to contractile failure in RV-PAB compared with LV-AOB.…”
Section: H704supporting
confidence: 92%
“…23 Some of these differences are detailed in the following text and are summarized in Table 2. [24][25][26][27][28][29][30][31][32][33][34] Likewise, there are differences in the RV response to certain effectors, including adrenergic hormones. Although α1-adrenergic agonists increase LV contractility, they may decrease RV contractility.…”
Section: Rv Versus LV Failure 1035mentioning
confidence: 99%
“…These metabolic changes may subsequently lead to hyperpolarization of the mitochondrial membrane potential in RV hypertrophy, inefficient energy metabolism, and increased lactate production at an earlier stage of maladaptation compared with the LV. 26 These molecular effects have potential therapeutic implications specific for the pressure-loaded RV. For example, dichloroacetate, Figure 2.…”
Section: Rv Versus LV Failure 1035mentioning
confidence: 99%
See 1 more Smart Citation
“…Current work in the field has advanced our understanding of RV myocyte pathobiology significantly in the context of pulmonary vascular disease, particularly with respect to maladaptive molecular mechanisms that modulate RV failure through changes in cellular metabolism, 10 nitric oxide bioavailability, 11,12 and ion channel dysfunction. 13 These basic and translational scientific models, which emphasize novel RV-specific targets to improve RV performance, have illuminated a number of cell-signaling pathways with future therapeutic promise for patients afflicted with pulmonary hypertension-induced RV dysfunction.…”
Section: Article See P 2859mentioning
confidence: 99%